Business Performance Measurement and Management 2009
DOI: 10.1007/978-3-642-04800-5_13
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of Performance Appraisal

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 24 publications
2
57
0
2
Order By: Relevance
“…Previous study has indicated that compatibility between the boss and the subordinates based on the same objectives can have a significant impact on performance appraisal. Through joint objective setting appraisees develop a feeling of ownership, which has a more powerful effect upon subsequent performance than just a general discussion about goals (Prowse & Prowse, 2009). Objectives setting allows employees to know up-front the standards by which their performance will be evaluated.…”
Section: Performance Appraisal Processmentioning
confidence: 99%
“…Previous study has indicated that compatibility between the boss and the subordinates based on the same objectives can have a significant impact on performance appraisal. Through joint objective setting appraisees develop a feeling of ownership, which has a more powerful effect upon subsequent performance than just a general discussion about goals (Prowse & Prowse, 2009). Objectives setting allows employees to know up-front the standards by which their performance will be evaluated.…”
Section: Performance Appraisal Processmentioning
confidence: 99%
“…According to [27], there are a great number of design features that potentially can influence the effectiveness of a performance management system, and many of these have been empirically studied to clarify their impact. Studies from [1,9,15,17,26] have shown that the major and prevalent problem confronting personnel appraisal is always the mistake that the rater often commits. Some of the mistakes are halo effects (this occurs when a manager appraises the performance of an employee based on a certain characteristic), error of contrast (this occurs when the rating of an employee is dependent on the performance of another person doing similar work), central tendency error (this occurs when a rater award all employees average or above average rating), leniency or strictness error (leniency occurs when the rater rate all employee high while strictness occurs when all employees are rated low), recency effect error (this occurs when rater allows recent occurrence to influence his judgement of an individual performance) and the proximity error (this occurs when a rater uses one technique to measure different traits in individual performance).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quite a number of challenges have been identified as confronting the effective and efficient practice of the performance appraisal system which includes the effect of reward and its turnout in commitment and loyalty of employees which triggers productivity within the organization. From past researches [13][14][15][16] and findings, it has been observed that matching both rewards as a result of employee's performance in an organization will commit employees more to the performance appraisal process [2] and showing them that the completion of the performance targets and objectives will affect them directly [17]. Organizations fail in motivating their employees especially those that have performed excellently well over a period of time leading to a negative attitude or response from employees [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations